Can gifts at marriage proxy for intrahousehold power? a non parametric analysis - Dacuycuy, Connie B.; Dacuycuy, Lawrence B. (2009)
The study employs a nonparametric procedure to ascertain the informational content of asset densities in understanding various intrahousehold issues faced by husbands and wives. Using survey data collected in Bangkadesh and employing s nonparametric tests, we find that gifts at marriage have informational content as proxy for intrahousehold power.